Unsaturated fatty acids and cancer - Skopińska-Różewska, Ewa; Sommer, Ewa; Sommer, Sylwester (Contemporary Oncology/Współczesna Onkologia, 2002)
Numerous epidemiological and animal experimental studies have shown the effect of polyunsaturated fatty acids (PUFAs) on tumorigenesis and metastasis. PUFAs are not synthesised in the body and have to be supplied in a diet. Linoleic acid (LA, C18:3, n-6 PUFA} that is metabolised in the body to arachidonic acid, the precursor of two families of prostanoids formed from cyclooxygenase and lipoxygenase mediated reactions enhances mammary, colon and prostate carcinogenesis. LA is present in large amounts in corn, sunflower, soy and evening primrose oils. Gamma-linolenic acid (GLA, C18:3, n-6 PUFA} which is found in the evening primrose and borage oils suppresses carcinogenesis. It has been also found that the diet rich in n-3 PUFAs suppresses carcinogenesis. N-3 PUFAs - eicosapentaenoic acid (EPA, C20:5) and docosahexaenoic acid (DHA, C22:6) are the components of fish oils. Although the exact mechanisms by which dietary fats induce or suppress carcinogenesis have not been identified, arachidonic acid derived - prostanoids are believed to play an important role in these processes. Some prostanoids regulate tumor growth and metastasis. In principle, the fatty acids provided in diets can be metabolized via two major routes: incorporation into membrane phospholipids of dividing tumor cells and formation of prostanoids and leukotrienes. Prostanoids originated from n-3 PUFAs can act as partial antagonists to the tumorigenic action of those derived from n-6 PUFAs and thus suppresses the proliferation of the tumor cells. Possible mechanism includes also a direct influence of dietary fats on hormone levels and host immune response which may in turn control tumor growth. To date few studies have assessed the influence of dietary fat on one of the most important factors for successful tumor growth and metastasis, that is vascularisation. Angiogenesis is crucial for both primary tumor growth as well as for metastasis. 12-hydroxyeicosatetraenoic acid {12-HETE}, product of lipoxygenase-mediated arachidonic acid has been identified as an angiogenic factor. It was found that LA enhanced angiogenesis but n-3 fatty acids present in fish oils may inhibit primary tumor growth through modulation of select determitants of angiogenesis. The possible role in carcinogenesis of CLA (conjugated linoleic acid) which is closely related to LA, was discussed.